Carta de José Celso Barbosa a Roberto H. Todd - Todd, Roberto H.; Celso Barbosa, José (My University, 1921)
Varios problemas en la legislatura.
Keywords: Puerto Rico--Politics and government.; Puerto Rico--Política y gobierno.; Tous Soto, José, 1874-1933; Barceló, Antonio R., 1868-1938; Córdova Dávila, Félix, 1878-1938